2007
DOI: 10.1590/s0021-75572007000800011
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de uma intervenção pró-aleitamento nas taxas de amamentação de recém-nascidos de muito baixo peso

Abstract: Objective: To describe an intervention to provide support and encouragement to mothers of preterm newborns and to evaluate its effect on breastfeeding rates in the first 6 months after hospital discharge. Methods:One hundred newborns and their mothers were selected consecutively and prospectively according to order of birth. The mother-infant dyads were alternately assigned to one of two groups: one group received routine care (routine group), and the other group received the intervention (intervention group).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…Mixed feeding was identified in our interviews as a widely adopted practice in feeding extremely premature babies. Similar to that found in this study, we observed that the mother of premature baby does not maintain exclusive breastfeeding when realizes that her child is not satisfied and/or not gaining weight (10,16) .…”
Section: Baby Feeding Schedule After Leaving the Maternitysupporting
confidence: 88%
See 1 more Smart Citation
“…Mixed feeding was identified in our interviews as a widely adopted practice in feeding extremely premature babies. Similar to that found in this study, we observed that the mother of premature baby does not maintain exclusive breastfeeding when realizes that her child is not satisfied and/or not gaining weight (10,16) .…”
Section: Baby Feeding Schedule After Leaving the Maternitysupporting
confidence: 88%
“…However, even though breastfeeding is the richest food for babies (9)(10) and that breast milk is the most appropriate food for them, many studies show low indicators related to this practice among us (1,9) .…”
mentioning
confidence: 99%
“…O início ou não da prática do AM e também outros momentos muito importantes constituíram em objetos de investigação sobre o , entre outros(DALL'OGLIO et al, 2007). Outra pesquisa identificou uma redução significativa na taxa de desmame de 64,3% no grupo controle (GC) para 19,5% no grupo de intervenção, devido ao aconselhamento e às orientações sobre ordenha para as mães participantes desse último grupo(SANTORO JÚNIOR;MARTINEZ, 2007). Constataram-se ainda, em um ensaio clínico aleatório, elevadas taxas de prevalência do AM no grupo que recebia estimulação oral e sucção nãonutritiva (grupo de intervenção), quando comparadas às taxas obtidas no GC(PIMENTA et al, 2008).…”
unclassified